EFEKTIVITAS PERENCANAAN ANGGARAN PADA SEKRETARIAT DPRD KABUPATEN SIKKA - Maria Rosa Oktaviani Toji; Emilianus Eo Kutu Goo; Kristiana Reinaldis Aek (Jurnal Projemen UNIPA, 2026)
This study aimed do analyse the level of effectivenss of thr budget planning process at the Secretariat of the Regional House of Representatives in Sikka Regency for the year 2024 and to assess the extent to which the budget planning prepared through the Work Plan and Budget Document (RKA) and the Budget Implementation Document (BID) proves effective. The research employed a descriptive qualitative method, with data collected through in-depth interviews, observation, and documentary study. The findings indicated that the budget planning process at the Secretariat of the Regional House of Representatives in Sikka Regency can be classified as reasonably effective. This effectiveness is evidenced by: (1) the alignment between planned programs and organisational needs, (2) the systematic preparation of budget documents, and (3) the existence of a verification process conducted by the Regional Government Budget Team which ensures that the planned budget is more target-oriented and accurate. Furthermore, the RKA and DPA documents have effectively served as operational guidelines for activity implementation and budget utilization throughout the fiscal year.